Advanced Epitaxial Lift‐Off and Transfer Procedure for the Fabrication of High‐Quality Functional Oxide Membranes (Adv. Mater. Interfaces 2/2023). Issue 2 (23rd January 2023) - Bouaziz, Jordan; Cancellieri, Claudia; Rheingans, Bastian; Jeurgens, Lars P. H.; La Mattina, Fabio
Abstract : Flexible Electronics In article number 2201458, Jordan Bouaziz, Fabio La Mattina, and colleagues describe the use of water‐soluble Sr3 Al2 O6 oxide to enable the fabrication of complex oxide membranes of a few tens of nanometers in size. The transfer of these membranes to other substrates opens the possibility of exploiting the countless oxide properties for the realization of new electronic devices.